REDUPLIKASI DALAM KUMPULAN CERPEN ATAVISME KARYA BUDI DARMA - Paradida, Yulia Putri; Ansiska, Paisal; Tarigan, Marsten Lihardo; Luhulima, Fiona Djunita Natalia (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Morphology focuses on elements related to word structure or word forms in language. Various morphological processes are present in morphological analysis, including the reduplication or repetition of word forms. Word repetition or reduplication is a method in which a grammatical unit is reapplied, either in whole or in part, whether there is a difference in sound. In this study, the approach adopted is a qualitative research method. This approach does not involve calculating numbers or statistics but focuses on analyzing data narratively. Therefore, the data used in this research comes from documents, especially the collection of short stories "Atavism" by Budi Darma. The data collected are quotations that include words, phrases, sentences, and discourses related to various forms of reduplication, including complete reduplication, sound-changing reduplication, partial reduplication, and compound reduplication. This study aims to conduct an in-depth analysis and comprehensively understand reduplication aspects in Budi Darma's "Atavism" short story collection, including complete reduplication, sound-changing reduplication, partial reduplication, and compound reduplication. Through this research, a clearer picture of the use and effect of reduplication in literary work can be achieved. Keywords: short story, morphology, reduplication